Blockchain-Driven Entrepreneurship: Catalyzing Business Innovation and Transformation - Shaikh, Engr. Dr. Muhammad Kashif; Naqavi , Syed Baqur; Tahir, Muhammad (Al-Qanṭara, 2025)
This study explores how digital technology on blockchain impacts entrepreneurial ventures and how technology changes transparency and builds up trust between businesses and their customers as well as their engagement through uncertainty from the government’s rules changes this relationship and how well businesses have prepared themselves to use this technology. Blockchain, originally a cornerstone for cryptocurrencies has transformed into a valuable asset in essence crucial for startup companies as well as ongoing/emerging businesses. The technology allows for what is secure, transparent and decentralized trading. It marks a major shift. Using Structural Equation Modeling (SEM) with data from 210 entrepreneurs and professionals, the study tests five hypotheses within a conceptual framework where blockchain technology is the independent variable, transparency and security are mediators, and customer trust and engagement are dependent variables. The results show that blockchain reinforces transparency and security wins for trust among customers and customer engagement in return. Furthermore, regulatory uncertainty negatively moderates these relationships, while digital infrastructure readiness strengthens them. These findings offer practical implications for entrepreneurs and policymakers by emphasizing the need for regulatory clarity and digital preparedness to fully realize blockchain’s potential. The study contributes to the growing literature on blockchain in entrepreneurship by providing empirical evidence and strategic insights for its effective integration into business models. And it concludes that when blockchain aligns itself nicely with major leaders and supported by supporting systems, it can really act as a dynamo that inspires and fuels new ideas and entrepreneurial success.